What is the recovery rate and risk of long-term consequences following a diagnosis of COVID-19? A harmonised, global longitudinal observational study protocol - Sigfrid, Louise (2021)
University of Oxford. Centre for Tropical Medicine and Global Heatlh. ISARIC Global Support Centre. Oxford, UK.